2016
DOI: 10.1371/journal.pone.0149082
|View full text |Cite
|
Sign up to set email alerts
|

Endurance Exercise Enhances the Effect of Strength Training on Muscle Fiber Size and Protein Expression of Akt and mTOR

Abstract: Reports concerning the effect of endurance exercise on the anabolic response to strength training have been contradictory. This study re-investigated this issue, focusing on training effects on indicators of protein synthesis and degradation. Two groups of male subjects performed 7 weeks of resistance exercise alone (R; n = 7) or in combination with preceding endurance exercise, including both continuous and interval cycling (ER; n = 9). Muscle biopsies were taken before and after the training period. Similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 62 publications
3
43
1
3
Order By: Relevance
“…This is in concert with recent data showing that the molecular signaling toward muscle hypertrophy are not blunted when high‐intensity interval cycling follows acute resistance exercise (Pugh et al., ). Furthermore, it seems that cycling exercise may provide an additional stimulation for muscle growth when combined with resistance exercise (Kazior et al., ). Muscle strength increased similarly after RE and REC which is in agreement with previous studies showing that strength increments are not impeded with the addition of aerobic exercise on a bicycle to resistance exercise (McCarthy et al., ; Hakkinen et al., ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in concert with recent data showing that the molecular signaling toward muscle hypertrophy are not blunted when high‐intensity interval cycling follows acute resistance exercise (Pugh et al., ). Furthermore, it seems that cycling exercise may provide an additional stimulation for muscle growth when combined with resistance exercise (Kazior et al., ). Muscle strength increased similarly after RE and REC which is in agreement with previous studies showing that strength increments are not impeded with the addition of aerobic exercise on a bicycle to resistance exercise (McCarthy et al., ; Hakkinen et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, both RE and REC induced significant decreases in the number of type IIX fibers which is consistent to those previous data. Training parameters seem to dictate the exact muscle fiber adaptations since it was recently reported that continuous and interval endurance cycling performed immediately before resistance training may result in decreases in the percentage of type I fibers with concomitant increases in their CSA (Kazior et al., ). The underlying mechanisms toward such fiber type alterations should be the focus of future research.…”
Section: Discussionmentioning
confidence: 85%
“…; Kazior et al . ). An important consideration when comparing the outcomes of studies of single mode versus concurrent exercise bouts is that more often than not, the contractile stimulus to the working muscles (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…Remarkably, all participants chose to perform both RE and endurance exercise components within a single session. However, there is evidence to suggest that combining RE and endurance exercise will impair strength development and muscle size (Hickson 1980 ; Craig et al 1991 ; Hennessy and Watson 1994 ; Coffey et al 2009a , b ; Babcock et al 2012 ; Kikuchi et al 2016 ; Fyfe et al 2016 ), although such evidence is equivocal (Bell et al 1991 ; Shaw et al 2009 ; Donges et al 2012 ; Lundberg et al 2012 , 2013 ; Apró et al 2013 ; Kazior et al 2016 ). We have recently shown that using an acute bout of high-intensity interval training (HIIT) in combination with RE, as an alternative to moderate-intensity endurance exercise with RE, does not impede acute (< 6 h) gene expression and protein signalling markers of muscle growth compared to a single bout of RE alone in young, healthy individuals (Pugh et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%